Mosaic art in Ancient Sepphoris : Between East and West - WEISS, Zeev
The paper presents several mosaics from Roman and Byzantine Sepphoris, and addresses the question of whether and to what degree the Antiochene tradition was influential in mosaic art in the Galilean city. Rather, they seem to point to a more complex trend that incorporates traditions from the East and the West – from Antioch and North Africa. (Excerpt from the author’s abstract.)
p. 941-952, 9 ill. n.b. et coul.Éditeur : Istanbul, Ege YayınlarıColloque : 2009, Bursa
Keywords: Bibliographie par pays, région ou ensemble géographique; Atelier de mosaïstes (Antioche [sur l'Oronte], TUR); Influence africaine; Influence byzantine; Byzance, byzantin (art, civilisation); Afrique du nord; Antioche, Antakya; Galilée; Sepphoris; Turquie